AN ANALYSIS OF DIRECTIVE SPEECH ACT IN THUNDERBOLT MOVIE: PRAGMATIC APPROACH - Febriany, Mariaty; Afriana, Afriana (Universitas Putera Batam, 2025)
The purpose of this study is to investigate the types of directive speech acts found in the movie Thunderbolt. This descriptive qualitative research focuses on the utterances produced by characters in the film, with direct speech acts serving as the main data source. Data were collected through an observational method using a non-participatory technique. The data analysis applied Sudaryanto’s (2015) method of identifying language elements, while the theoretical framework was based on Searle’s (1979) classification of directive speech acts. The findings show that the characters frequently employed directive speech acts to influence others’ actions. Out of 57 identified utterances, 20 were categorized as asking, 15 as requesting, 5 as ordering, 5 as commanding, 5 as giving advice, 5 as begging, and 2 as inviting. The most dominant type was asking. These speech acts were primarily used to give instructions, request help, and express urgency, especially in high-pressure scenes. This research offers insights into the use of directive speech acts in film dialogues and highlights their relevance to real-world communication and interaction.